Correlative analysis of blood pressure and other biochemical parameters with type 2 DM subjects (Northern International Medical College Journal, 2015)
Objective : To determine the association of blood pressure and other biochemical parameters with type 2 DM subjects.Methodology : This was an observational study with case control design was conducted in the Biomedical Research Group, Research Division, Bangladesh Institute of Research and Rehabilitation in Diabetes ,Endocrine Metabolic Disorders (BIRDEM), Dhaka Bangladesh, during the period of July 2008 to June 2009. A total of 153 subjects were included in study of which 63 belonged to T2 Diabetes Mellitus group and 90 were healthy Controls. Insulin glucose ratio were assayed in patients and controls and identified the association, using standardized assay methods. We also assessed the type 2 diabetic patients who had significantly raised Fasting blood sugar, insulin HOMA-B %= B cell function assessed by homeostasis model assessment to compared with the healthy controls. Correlation analysis of HOMA-B % with biochemical parameters, blood pressure, fasting and post prandial glucose also analysed.Results : Age of Control and type 2 DM subjects ( Mean±SD),P-value] were (46 ± 8.31) and (47 ±7.58), (P=0.326) respectively and BMI, among subject and control (kg/m2), (Mean ± SD), (24 ± 3.96, 25 ± 2.72 p=0.754). WHR [cm, (Mean±SD), p=